1993
DOI: 10.3109/00365529309090245
|View full text |Cite
|
Sign up to set email alerts
|

Gastrectomy Causes Bone Loss in the Rat: Is Lack of Gastric Acid Responsible?

Abstract: Total gastrectomy or resection of the acid-producing part of the stomach (fundectomy) in the rat induced a marked and rapid reduction in bone wet weight, ash weight, and density (expressed as ash weight in mg/mm3 bone). Bone volumes were also affected but not as much. The radius, sternum, tibia, and femur were studied. Three weeks after gastrectomy the bone ash weight was reduced by almost 30% and the density by more than 25%. Maximum bone loss (approximately 40%) occurred about 6 weeks after the operation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 25 publications
3
52
2
Order By: Relevance
“…It may be argued that removal of the acid-producing part of the stomach may cause acidosis and affect calcium/bone metabolism. However, complete inhibition of gastric acid secretion by proton pump inhibitors does not cause osteopenia (Persson et al 1993). The findings support the view that the stomach is important for bone metabolism by mechanisms that are unrelated to dietary deficiencies or lack of gastric acid (see Surve et al 2002).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It may be argued that removal of the acid-producing part of the stomach may cause acidosis and affect calcium/bone metabolism. However, complete inhibition of gastric acid secretion by proton pump inhibitors does not cause osteopenia (Persson et al 1993). The findings support the view that the stomach is important for bone metabolism by mechanisms that are unrelated to dietary deficiencies or lack of gastric acid (see Surve et al 2002).…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, it seems unlikely that either GX-induced or OVX-induced osteopenia results from generalized nutritional deficiency, as neither the GX rats nor the OVX rats were growth retarded (see Surve et al 2001a, b, Andersson et al 2002. Moreover, a specific deficiency of calcium is unlikely since it has been shown earlier that calcium supplements have no effect (Persson et al 1993, Klinge et al 1995. Vitamin D deficiency is known to cause impaired calcium absorption and osteomalacia.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the importance of gastrectomy-induced osteoporosis, very little is known about the influence of the gastric mucosa on bone metabolism. Since the experimental studies of IVY (15) , who described bone loss in gastrectomized dogs, many studies have demonstrated that the gastric mucosa is related in some way to the incorporation of calcium into bone (19,20,23,31,32,37) . Despite the accepted role of gastric acid secretion in maintaining calcium absorption, the treatment of rats with a potent proton pump inhibitor resulting in almost complete achlorhydria had no effect on bone density, and, in addition, parenteral calcium supplementation did not prevent bone mineral loss in gastrectomized animals (32) .…”
Section: Bone Mineral Density Gastric Mucosa Atrophy and Hp Infectionmentioning
confidence: 99%
“…First, gastric acid is thought to dissolve insoluble calcium in the diet, thereby facilitating the absorption of calcium from the small intestine (4-7). Second, hypocalcinocemic gastric peptide hormone, released from the stomach in response to gastrin, is thought to enhance the uptake of calcium into bone (2,8). Third, the rate of delivery of calcium to the small intestine from the stomach is considered a potentially important determinant of calcium absorption (9,10).…”
Section: Discussionmentioning
confidence: 99%